Antenna Pattern Diversity using EBG - Mohamad Isa, Mohd Sa'ari (2010)

(untitled)
A conformal patch antenna operating in the TM01 mode is integrated over an electromagnetic bandgap surface (EBG) to provide a beam scanning antenna. The circular EBG elements are arranged in a sector pattern and the vias on each sector of the EBG are switched in and out to steer the beam into that sector. The reflection coefficients for the antenna when the vias are switched remain stable and experimental results validate the simulations. Overall a flexible beam scanned antenna is demonstrated.